Financial Statement Preparation Skills for Business Actors Using Applications - Edan, Thamir Salih (Community Service Akseprin Journal, 2023)
The digital era that is full of technological developments must be utilized to increase the profits of micro and small businesses. One of the efforts is to utilize an android application to record transactions. Some business actors do not understand the use of this application. The purpose of this community service is to increase awareness and skills of business actors in utilizing the android-based financial application "SME Accounting" to produce financial statements. The target subjects of student activities are some of which are business actors. The method used is service learning which involves presenting material (lectures) and mentoring. The lecture is intended to convey theory and is accompanied by questions and answers and followed by a demonstration of SME Accounting applications. Assistance is carried out in practice sessions filled with case resolution. The process of operating the SME Accounting application runs well. The training is able to improve participants' skills in operating android-based applications. This is evidenced through the actions of students before and after getting to know the Application for SMEs. Before the team conducted an application demonstration and mentoring, participants had difficulty in inputting transactions but after the demonstration and mentoring were carried out, participants were able to input transactions independently and enthusiastically.